Pengembangan Buku Saku Kimia Materi Stoikiometri - Aida Fitri Isnaini; Mukhtar Haris; Dodiy Firmansyah (FKIP University of Mataram, 2026)
This study was motivated by students' difficulties in understanding stoichiometry material, which is abstract and involves many calculations, thus requiring practical, concise, and easy-to-use learning media. This study aims to test the validity, reliability, and practicality of the developed chemistry pocketbook on stoichiometry material. The research method used is Research and Development (R&D) with a 4D development model that includes the stages of define, design, develop, and disseminate. The subjects of this study consisted of chemistry education lecturers at FKIP University of Mataram, and chemistry teachers from SMAN 1 Labuapi for the purposes of validating the pocketbook and 18 students of class XI A of SMAN 1 Labuapi for the purposes of testing the practicality of the pocketbook. The data collection technique used was a questionnaire. The data analysis technique used the Aiken's V formula to calculate expert validation, the Pearson Product Moment formula to calculate empirical validation, Percentage Agreement to measure the reliability of the pocketbook and Cronbach's Alpha to measure the reliability of the practicality, and a practicality percentage analysis to assess students' responses to the pocketbook. The results of the study showed that the expert validity value was in the valid category (V = 0.74), the reliability of pocketbook was 97% in the excellent category, and the practicality of the pocketbook received an average of 88% with a very practical category. Thus, it can be concluded that the developed chemistry pocketbook on stoichiometry material is suitable for use as a learning media that can help students understand the basic concepts of stoichiometry more easily, interestingly, and efficiently.